Phase 1 trial of a 20-valent pneumococcal conjugate vaccine in healthy adults. Issue 42 (30th September 2019) - Thompson, Allison; Lamberth, Erik; Severs, Joseph; Scully, Ingrid; Tarabar, Sanela; Ginis, John; Jansen, Kathrin U.; Gruber, William C.; Scott, Daniel A.; Watson, Wendy
Abstract: Introduction: Streptococcus pneumoniae is a leading cause of bacteremia, bacterial pneumonia, and meningitis, and is associated with substantial morbidity and mortality, particularly in those under 2 years of age and those over 65 years of age. While significant progress against S. pneumoniae -related disease has been made as a result of the introduction of pneumococcal conjugate vaccines (PCV7, PCV10 and PCV13), there remains value in further expanding pneumococcal vaccine serotype coverage. Here we present the first report of a 20-valent pneumococcal conjugate vaccine (PCV20) containing capsular polysaccharide conjugates present in PCV13 as well as 7 new serotypes (8, 10A, 11A, 12F, 15B, 22F, and 33F) which are important contributors to pneumococcal disease. Methods: This Phase I first-in-human study was a randomized, controlled, observer-blinded study with a two-arm parallel design to assess the safety, tolerability, and immunogenicity of PCV20 in adults. A total of 66 healthy adults 18–49 years of age with no history of pneumococcal vaccination were enrolled and randomized to receive a single dose of PCV20 or a licensed tetanus, diphtheria, acellular pertussis combination vaccine (Tdap) control. Local injection site reactions, select systemic symptoms, laboratory studies, and adverse events were assessed. Opsonophagocytic activity (OPA) titers and IgG concentrations were measured in sera collected prior to, and approximately one month (28–35 days) after vaccination. Results: Vaccination with PCV20 elicited substantial IgG and functional bactericidal immune responses as demonstrated by increases in IgG geometric mean concentrations (GMCs) and OPA geometric mean titers (GMTs) to the 20 vaccine serotypes. The overall safety profile of PCV20 was similar to Tdap, and generally consistent with that observed after PCV13 administration. Conclusions: Vaccination with PCV20 was well tolerated and induced substantial functional (OPA) and IgG responses to all vaccine serotypes. There were no safety issues identified in this Phase 1 study, and the data supported further evaluation of PCV20.